Tugas dan Tanggung Jawab Tenaga Kependidikan Dalam Lingkungan Manajemen Pendidikan - Suntani, Utui Tatang (Yayasan Sembilan Pemuda Indonesia, 2022)
The implementation of an educational institution such as a school requires competent human resources in their field. For administrative and managerial activities, it is impossible to leave it entirely to the teacher. This is because teachers have their own portion in the teaching and implementation of education. Thus, it takes human resources who have competence in the managerial field. This article aims to describe the duties and responsibilities of school education staff using the literature study method. Research issues that arise due to managerial inequality are discussed theoretically and practically in the field based on published journal articles. The results of research tracking found that education personnel have overly complex tasks and responsibilities. Not only in the managerial field, but also providing motivation for educators to be in an orderly administration so that they also help in the overall school administration process.